2014
DOI: 10.5489/cuaj.1721
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological analysis of renal cell carcinoma demonstrates decreasing tumour grade over a 17-year period

Abstract: Introduction: Renal cell carcinoma (RCC) represents about 3% of adult malignancies in Ireland. Worldwide there is a reported increasing incidence and recent studies report a stage migration towards smaller tumours. We assess the clinico-pathological features and survival of patients with RCC in a surgically treated cohort. Methods: A retrospective analysis of all nephrectomies carried out between 1995 and 2012 was carried out in an Irish tertiary referral university hospital. Data recorded included patient dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The patients with organ confined tumours (pT1 and pT2) have decreased from 83.6 to 72.5%, in the contrary, pT1b tumours were increased from 24.4 to 29.7% in our study. The authors reported that the incidence of organ confined tumour was increased from 36.9 to 73.2% during the 27 years (Pichler et al, 2012); the other study demonstrated that the percentage of organ confined tumours was 66.7, 56.2 and 65.6% in the three study group respectively (Nason et al, 2014). The patients with local advanced tumours (pT3 and pT4) have increased during the study period (from 16.2 to 27.3%).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The patients with organ confined tumours (pT1 and pT2) have decreased from 83.6 to 72.5%, in the contrary, pT1b tumours were increased from 24.4 to 29.7% in our study. The authors reported that the incidence of organ confined tumour was increased from 36.9 to 73.2% during the 27 years (Pichler et al, 2012); the other study demonstrated that the percentage of organ confined tumours was 66.7, 56.2 and 65.6% in the three study group respectively (Nason et al, 2014). The patients with local advanced tumours (pT3 and pT4) have increased during the study period (from 16.2 to 27.3%).…”
Section: Discussionmentioning
confidence: 87%
“…The authors observed a decrease in pathological pT3 and pT4 RCC patients from 29.1 to 20.5% over two decades (Gupta et al, 2010). The patients with local advanced RCC have increased during the seventeen years period (from 33.3 to 34.4%) in another study (Nason et al, 2014). One of the reasons of increasing numbers of patients with local advanced tumour: our hospital is tertiary referral centre.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…37 This has led to a stage migration overall towards lower stage of disease at time of diagnosis. 38 In order to provide clinically-meaningful interpretations of PLT/WBC ratio, we used quintiles. However, future research may identify more informative ways to operationalize this variable such as a dichotomous threshold.…”
Section: Cuaj -Original Research Garbens Et Al: Wbc-plt Ratio Predictmentioning
confidence: 99%
“…1 Newer series such as this one have renewed value in that they may provide a window into RCC outcomes in an era when the peculiarities of the small renal mass (SRM) have gained prominence. 2 The increasing incidence of RCC, attributed in large part to increased abdominal imaging, has typically accompanied a downward stage migration, with smaller incident masses and the expectation of lower stage and grade.…”
mentioning
confidence: 99%